Text Choice Adequacy in a Romanian Language Textbook for Hungarian Minority Students - Imola Katalin Nagy; Gabriella Kovács (Acta Universitatis Sapientiae: Philologica)
Teaching Romanian language to Hungarian ethnic minority students in Romania has been a matter of debate for a long time Some teachers and experts suggest that Romanian textbooks are inadequate and fail to meet the needs of minority students, while others argue that they are sufficient and serve the purpose of teaching the Romanian language to nonnative speakers An appropriate choice of texts can support the development of language skills and cultural understanding, while inappropriate choices can hinder them In this study, we propose to investigate the texts in a Romanian language textbook written and approved for 7th-grade Hungarian minority students regarding the adequacy of topics and vocabulary in comparison with text choices in a textbook designed for teaching Romanian as a foreign language We propose to analyse and compare the texts from the following viewpoints: use of literary and non-literary texts; adequacy of the vocabulary and text adaptation; relevance and adequacy of topics; appropriacy of texts and activities.